(untitled) (Annals of Medical Research, 2021)
Aim: This study analyzed outcomes after short-segment pedicle screw-based semi-rigid stabilization with Poly (etheretherketone) (PEEK-polymer) rods in elderly patients with degenerative lumbar scoliosis. To date, there is no high level of evidence (Level-I) in the relevant literature. Therefore, this is the initial report about use of PEEK-polymer rods in elderly patients with degenerative lumbar scoliosis.Material and Methods: From January 2015 to June 2017, 31 patients aged over 60 years with degenerative lumbar scoliosis, who underwent pedicle screw-based semi-rigid stabilization with PEEK-polymer rods were investigated. All medical records and radiological images were reviewed to evaluate surgery-related complications and clinical outcomes.Results: Patients demonstrated clinically significant functional improvement (Oswestry Disability Index) with an average of 69.3% during an average follow-up of 36.1 months (range, 24–54 months) after surgery. Patients displayed significant Visual Analog Scale (VAS) improvements when comparing pre- and postoperative scores at an average change of 76% and 80% for VAS for back pain and leg pain, respectively. No neurological deficit was observed after surgery.Conclusion: Satisfactory percentage in functional and pain improvement as well as low rate of instrument-related complications was obtained after pedicle screw-based stabilization with PEEK-polymer rods. This system can now be considered a viable option in elderly patients with the degenerative lumbar scoliosis.